Vancomycin-resistant Enterococcus faecium: a national wide genomic snapshot in Switzerland - Dominique S. Blanc; Florian Mauffrey; Andrea C. Büchler; Danielle Vuichard-Gysin; Vanja Piezzi; Céline Gardiol; Marc Garcia; Trestan Pillonel; Laurent Poirel; Patrice Nordmann; Pascal Schlaepfer; Claudio Neidhöfer; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Multi-scale Study of the Effect of a Living Yeast-Based Biostimulant on Soybean - Marie Chambard; Anouk Lyver; Mohamed Amine Ben Mlouka; Benjamin Albert; Camille Profizi; Elodie Cusset; Jean-Christophe Avice; Pascal Cosette; Isabelle Trinsoutrot-Gattin; Isabelle Boulogne; Mélanie Bressan (Journal of Plant Growth Regulation, 2026)

Influence of Termite Diversity on Soil Properties and Silicon Dynamics. A Case Study in the Angkor Forest, Cambodia - Albert Juliette; Meunier Jean-Dominique; Muon Ratha; Syaukani Syaukani; Jouquet Pascal (Journal of Soil Science and Plant Nutrition, 2025)

Effects of wind turbine dimensions on the collision risk of raptors: A simulation approach based on flight height distributions - Tonio Schaub; Raymond H.G. Klaassen; Caroline De Zutter; Pascal Albert; Olivier Bedotti; Jean-Luc Bourrioux; Ralph Buij; Joël Chadœuf; Celia Grande; Hubertus Illner; Jérôme Isambert; Kjell Janssens; et al. (Science of The Total Environment, 2024)

Olivine-catalyzed glycolaldehyde and sugar synthesis under aqueous conditions: Application to prebiotic chemistry - Vassilissa Vinogradoff; Vanessa Leyva; Eric Mates-Torres; Raphael Pepino; Grégoire Danger; Albert Rimola; Lauryane Cazals; Coline Serra; Robert Pascal; Cornelia Meinert (Earth and Planetary Science Letters, 2024)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Pan-European inter-laboratory studies on a panel of in vitro cytotoxicity and pro-inflammation assays for nanoparticles - Jean-Pascal Piret; Olesja M. Bondarenko; Matthew S. P. Boyles; Martin Himly; Ana R. Ribeiro; Federico Benetti; Caroline Smal; Braulio Lima; Annegret Potthoff; Monica Simion; Elise Dumortier; Paulo Emilio C. Leite; et al. (Archives of Toxicology, 2017)

Molecular evolution and transcriptional regulation of the oilseed rape proline dehydrogenase genes suggest distinct roles of proline catabolism during development - Pascal Faës; Carole Deleu; Abdelkader Aïnouche; Françoise Le Cahérec; Emilie Montes; Vanessa Clouet; Anne-Marie Gouraud; Benjamin Albert; Mathilde Orsel; Gilles Lassalle; Laurent Leport; Alain Bouchereau; et al. (Planta, 2015)

Human proximity and habitat fragmentation are key drivers of the rangewide bonobo distribution - Jena R. Hickey; Janet Nackoney; Nathan P. Nibbelink; Stephen Blake; Aime Bonyenge; Sally Coxe; Jef Dupain; Maurice Emetshu; Takeshi Furuichi; Falk Grossmann; Patrick Guislain; John Hart; et al. (Biodiversity and Conservation, 2013)

Nitrogen availability impacts oilseed rape (Brassica napus L.) plant water status and proline production efficiency under water-limited conditions - Benjamin Albert; Françoise Le Cahérec; Marie-Françoise Niogret; Pascal Faes; Jean-Christophe Avice; Laurent Leport; Alain Bouchereau (Planta, 2012)